Implementation of Biochar-Supported Fish Smoking Technology as A Green Technology Model for Sustainable Coastal Community Economy - Khairiah Khairiah; Junita Putri Rajana Harahap; Hamin Ahmad Hamin Ahmad; Daffa Raihan; Fisikanta Bukit Fisikanta Bukit; Sutri Novika (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: Traditional fish smoking practices in coastal communities still rely heavily on firewood and conventional smoking systems, resulting in excessive smoke emissions, inefficient fuel consumption, and environmental pollution. This community service program introduced biochar-supported fish smoking technology as a green technology innovation to strengthen sustainable coastal community economies. Contribution: This program contributes an integrative and replicable community empowerment model that combines biochar-based green technology, entrepreneurship strengthening, and digital marketing transformation within cross-country coastal communities. Methods: The program was implemented in Bintang Meriah Village, Langkat Regency, North Sumatra, Indonesia, and Kuala Kedah, Malaysia, involving 28 participants from fish-smoking SMEs and coastal community groups. Activities were conducted through socialization, training, technology application, and mentoring. Results: The implementation of biochar-supported fish smoking technology reduced firewood consumption by approximately 26%, decreased smoke emissions by around 30%, and improved production efficiency by approximately 24%. Approximately 68% of participants successfully adopted digital marketing platforms for product promotion and business expansion. Conclusion: The integration of biochar-supported fish smoking technology and community empowerment successfully improved environmental sustainability, production efficiency, and local economic resilience.